Coronary Thrombosis in a Patient with COVID-19 Who Was on Anticoagulant Therapy. - Hatamnejad, Mohammad Reza; Tafti, Farima Fallah; Abdi, Alireza; Boogar, Shahrokh Sadeghi; Bazrafshan, Hamed (International Cardiovascular Research Journal, 2021)
Introduction: COVID-19-related thrombotic events are associated with an increase in the risk of mortality and morbidity. Considering the research on the pathophysiology of the disease, the significance of cardiac thrombosis is being more recognized. Case Presentation: This study aimed to present the first case report of a Left Main Coronary Artery (LMCA) thrombosis due to COVID-19 infection in a middle-aged male with a mechanical valve on anticoagulant therapy and with an International Normalized Ratio (INR) within the therapeutic range. Conclusions: The results suggested that the therapeutic INR range may need to be higher (about 3.5) during the acute phase of COVID-19 infection to prevent thrombotic events amongst patients with COVID-19 who are on anticoagulant therapy. However, further evidence is required to determine the target range for INR in patients with COVID-19 who are on anticoagulants prior to infection.